ESTABLISHMENT OF 6 AGRICULTURAL REGIONAL CENTERS IN REPUBLIC OF SRPSKA - Turalić, Fuad; Dardić, Mile; Trkulja, Vojislav; Cvijić, Vlado; Zrnić, Mirela (Economics of Agriculture, 2011)
The Program represents joint concept of Agricultural Institute of Republic of Srpska, Farm Collective Association and NGO "Krajina" with aim of establishing, realizing and conducting strategic aims of Government of RS. Through this Program Agriculture is realized, organic production of fruit and vegetables is established and conducted, husbandry cultures are grown, Medical herbs, aromatic herbs, forestall fruits and spices are processed and placed onto the market, products are certifed and products are market placed for already known buyer. The Program includes organization and equipment of 6 regional centers for production, processing and distribution. Those six centers are fallowing ones: Krajina/ Potkozarje, Posavina/Ozren, Semberija/Majevica, Romanija/Podrinje, Hercegovina and Birač region. Agricultural Institute of RS is providing expert and scientifcally resources. Farm Collective Association of RS is providing function of Municipal centers (in fallowing text referred as ACC – Agricultural Collective Center) in sense of monitoring of receiving and distributing of materials, its effective use, production monitoring, taking over fnal products, storing, fnal and additional processing, preparation for distribution to regional agricultural centers. The role of NGO "Krajina" is reflected in providing and conducting all necessary education in cooperation with theirs partners, organization and application of effcient production, product standardization through by introducing HACCP and ISO standards for food safety and quality standards, as well as EUROGAP standards. Partners (Municipalities) (47 Municipalities are included by this program). They are assuring expert, fnancial and administrative implementation of the program, through their budgets for development and stimulation of organic agricultural production on area of their own Municipality through ACC – Agricultural Collective Center.